System modelling and characteristic research of novel high water-based synchronous lubrication piston pump - Hao JIANG; Lang YU; Yongkang LI (Meitan kexue jishu)
Expanding the speed range of high water-based piston pump is beneficial to the wide intelligent control of liquid supply system in fully mechanized coal mine. Aiming at the speed limitation of high water-based piston pumps caused by insufficient lubrication of key friction pairs under traditional low-pressure lubrication conditions, the group developed a high water-based piston pump structure and its synchronous lubrication method based on a stepped plunger to meet the high-speed operation. In order to deeply understand the system characteristics and synchronous lubrication effect of the friction pair, a system co-simulation model based on the software AMESim/Simulink is built to study the dynamic coupling characteristics between the lubrication and the working cavity, as well as the oil film characteristics of the slipper pair, which can reflect the lubrication effect of the friction pair under synchronous lubrication conditions. Further, the influence of pump speed on it is discussed. Finally, the flow characteristics of high water-based piston pump at high speed were tested by prototype test. The results show that the proposed synchronous lubrication method can produce lubricating oil in the lubrication chamber with increasing speed. With the increase of pump speed, the thickness of slipper auxiliary film decreases, and the extension of static pressure action time causes the increase of leakage. The oil film thickness of slipper boots ranges from 8.1 to 17.5 μm at the speed range of 500 to 2 000 r/min, meeting the needs of fluid lubrication. The experimental results show that when the speed is 500 r/min and 1 500 r/min, the deviation of the simulated and experimental average output flow of the piston pump is about 7.8% and 8.1%, respectively. The flow pulsation increases with the increase of the speed, and the measured flow pulsation is smaller than the numerical calculation result. The novel high water-based piston pump meets the demands of high-speed operation. Meanwhile, the establishment of pressure in the piston working chamber and lubrication chamber, as well as the opening and closing of the suction and discharge valves will have a hysteresis relative to the plunger movement, and become manifest with the increased pump speed, thus affecting the system volumetric efficiency and flow rate of pulsation. The research results verify the feasibility of the new synchronous lubrication high water-based piston pump applied to the high-speed conditions, and the causes of existing problems are analyzed, which will lay a theoretical and experimental basis for subsequent improvement and optimization.